SAMTALEN SOM INTERVIEW: At tale om kulturelle artikulationer i Kina - Larsen, John A. (Tidsskriftet Antropologi, 1995)
John A. Larsen: Conversation as Interview. Talking about Cultural Articulations in China In the beginning of the article the theoretical interest in the problems conceming the cultural articulation of the minority group is presented as the context for the methodological thematic. On the basis of fieldwork among the minority group Naxi in Southwestem China this article examines the advantages of viewing field conversations as different kinds of interviews. Three interview types are presented taking into account the formal, systematic properties as the situations under which the interviews took place. Through the article more general problems conceming the status of the fieldworker and the use of interpreters are discussed. It is argued that the understanding of data generating conversations as type of interview allows for a greater awareness of the formal information as well as the discourses within which this information is articulated. This more systematic approach to the production and analysis of field conversations has pro- ved to be especially fruitful in the unveiling of the discourses and processes behind an articulation of the minority culture, which has been the analytic aim of this investigation.